Gasto de la contraloría general de la república y su relación con el gasto del gobierno nacional periodo 2019 – 2023 - Enriquez Vela, Danika Melissa (2025)
State financing for the Comptroller General of the Republic is crucial in control activities and the fight against corruption by guaranteeing the independence and autonomy of the oversight bodies. At the same time, determining expenses helps with transparency and accountability. Due to this, the present study aims to identify the relationship between the expenditure of the Comptroller General of the Republic and the expenditure of the National Government for the period 2019 - 2023 with a correlational level, of a non-experimental design with a quantitative approach, identifying that between 2019 and 2023, the relationship between the expenditure of the Comptroller General of the Republic and the expenditure of the National Government for the period 2019 – 2023 is significant and positive. The investigation concludes that the analysis of the relationship between the expenses of the Comptroller General of the Republic and the National Government in the period 2019-2023 shows a statistically non significant correlation between their main spending items. The most notable relationship is found in expenses on goods and services, where the correlation is strong and significant, suggesting an alignment in the behavior of these expenses between the comptroller's office and national spending. In the case of personnel and capital expenditure, although positive correlations are observed, they do not reach statistical significance. Furthermore, the descriptive analysis reveals sustained growth in spending in both the Comptroller's Office and the National Government, with a notable increase in 2023, especially in spending on personnel and goods and services, reflecting an expansive trend in the allocation of resources. public in recent years.